Insights into the Structure of the Spruce Budworm (Choristoneura fumiferana) Genome, as Revealed by Molecular Cytogenetic Analyses and a High-Density Linkage Map - Picq, Sandrine; Lumley, Lisa; Šíchová, Jindra; Laroche, Jérôme; Pouliot, Esther; Brunet, Bryan M T; Levesque, Roger C; Sperling, Felix A H; Marec, František; Cusson, Michel (G3 (Bethesda, Md.), 2018)
Genome structure characterization can contribute to a better understanding of processes such as adaptation, speciation, and karyotype evolution, and can provide useful information for refining genome assemblies. We studied the genome of an important North American boreal forest pest, the spruce budworm, Choristoneura fumiferana, through a combination of molecular cytogenetic analyses and construction of a high-density linkage map based on single nucleotide polymorphism (SNP) markers obtained through a genotyping-by-sequencing (GBS) approach. Cytogenetic analyses using fluorescence in situ hybridization methods confirmed the haploid chromosome number of n = 30 in both sexes of C. fumiferana and showed, for the first time, that this species has a WZ/ZZ sex chromosome system. Synteny analysis based on a comparison of the Bombyx mori genome and the C. fumiferana linkage map revealed the presence of a neo-Z chromosome in the latter species, as previously reported for other tortricid moths. In this neo-Z chromosome, we detected an ABC transporter C2 (ABCC2) gene that has been associated with insecticide resistance. Sex-linkage of the ABCC2 gene provides a genomic context favorable to selection and rapid spread of resistance against Bacillus thuringiensis serotype kurstaki (Btk), the main insecticide used in Canada to control spruce budworm populations. Ultimately, the linkage map we developed, which comprises 3586 SNP markers distributed over 30 linkage groups for a total length of 1720.41 cM, will be a valuable tool for refining our draft assembly of the spruce budworm genome.
Keywords: Genome, Insect; Polymorphism, Single Nucleotide; Multidrug Resistance-Associated Proteins; chromozomy hmyzu; protein spojený s mnohočetnou rezistencí k lékům 2; Chromosomes, Insect; Multidrug Resistance-Associated Protein 2; Synteny; neo-Z chromosome; hmyzí proteiny; jednonukleotidový polymorfismus; Female; genom hmyzu; rezistence k insekticidům; Choristoneura fumiferana; syntenie; zvířata; Genetic Linkage; karyotype; ženské pohlaví; Male; proteiny spojené s mnohočetnou rezistencí k lékům; Insecticide Resistance; genetická vazba; genotyping-by-sequencing; Lepidoptera; Animals; mužské pohlaví; linkage map; Insect Proteins